Chemical characterization and cytotoxic activity evaluation of Lebanese propolis - Faour, Wissam H. (2017)
Chemical composition, anti-proliferative and proapoptotic activity as well as the effect of various fractions of Lebanese propolis on the cell cycle distribution were evaluated on Jurkat leukemic T-cells, glioblastoma U251 cells, and breast adenocarcinoma MDA-MB-231 cells using cytotoxic assays, flow cytometry as well as western blot analysis. Liquid chromatography-tandem mass spectrometry (LC–MS/MS) analysis revealed that ferulic acid, chrysin, pinocembrin, galangin are major constituents of the ethanolic crude extract of the Lebanese propolis, while the hexane fraction mostly contains chrysin, pinocembrin, galangin but at similar levels. Furthermore chemical analysis was performed using gas chromatography-mass spectrometry (GC–MS) to identify major compounds in the hexane fraction. Reduction of cell viability was observed in Jurkat cells exposed to the ethanolic crude extract and the hexane fraction, while viability of U251 and MDA-MB-231 cells was only affected upon exposure to the hexane fraction; the other fractions (aqueous phase, methylene chloride, and ethyl acetate) were without effect. Maximum toxic effect was obtained when Jurkat cells were cultivated with 90 μg/ml of both the crude extract and hexane faction. Toxicity started early after 24 h of incubation and remained till 72 h. Interestingly, the decrease in cell viability was accompanied by a significant increase in p53 protein expression levels and PARP cleavage. Cell cycle distribution showed an increase in the SubG0 fraction in Jurkat, U251 and MDA-MB-231 cells after 24 h incubation with the hexane fraction. This increase in SubG0 was further investigated in Jurkat cells by annexinV/PI and showed an increase in the percentage of cells in early and late apoptosis as well as necrosis. In conclusion, Lebanese propolis exhibited significant cytotoxicity and anti-proliferative activity promising enough that warrant further investigations on the molecular targets and mechanisms of action of Lebanese propolis.